A aplicação dos recursos da seguridade social, a partir da perspectiva da teoria dos sistemas, da teoria comunicacional e do caos - Zarzana Júnior, Dávio Antonio Prado (2011)
This work, focusing on the financing of Social Security, intends to conduct three checks: first, the existence of deviations in the application of the funds raised for this financing, including from a formulation of one concept of deviation. Second, to examine potential imbalances produced by these possible deviations, from the perspective of Systems Theory, using, in addition, terminology from Communicational Theory. And third, to probe the possibility of complementary application of Chaos Theory to the problem of deviations, if found. The overall result of these investigations, through the dialecticalempirical method, will contribute to the perception of the importance of compliance with the constitutional application of resources to finance the Social Security